2020
DOI: 10.1080/02673843.2020.1746675
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge is not enough: barriers and facilitators for reducing road traffic injuries amongst Indian adolescents, a qualitative study

Abstract: Road traffic injuries are a leading cause of death and injury amongst Indian adolescents. Our study sought to understand barriers and facilitators for reducing road traffic injury among Indian adolescents and to identify community perspectives on future solutions. Twenty-one face to face interviews and five focus group discussions were held with a wide range of stakeholders. The interviews were thematically analysed by two researchers. Poor roads, lack of transportation alternatives and low levels of law enfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…The finding that adolescents who had parental permission to cross main roads alone had greater odds of RTIs is consistent with previous studies that conclude that the number of streets crossed by adolescents is associated with injury 35. In addition, a qualitative study from India—a neighbouring country of Pakistan with a similar road environment—reported that adolescents displayed various distracted behaviours as pedestrians, such as using earphones and mobile phones as well as talking and playing with friends 36. Both the distracted behaviours and the unsafe road environment for pedestrians in Pakistan could be linked to an increased risk for RTIs.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that adolescents who had parental permission to cross main roads alone had greater odds of RTIs is consistent with previous studies that conclude that the number of streets crossed by adolescents is associated with injury 35. In addition, a qualitative study from India—a neighbouring country of Pakistan with a similar road environment—reported that adolescents displayed various distracted behaviours as pedestrians, such as using earphones and mobile phones as well as talking and playing with friends 36. Both the distracted behaviours and the unsafe road environment for pedestrians in Pakistan could be linked to an increased risk for RTIs.…”
Section: Discussionsupporting
confidence: 89%
“…It is well-known that knowledge is not enough to achieve behavior changes. 12-14 The gap between knowledge and practice has been identified in many settings and has led to a variety of behavior changes in models relating to health. 15 One reason for the lack of behavior changes is the lack of understanding of the context in which the behavior occurs.…”
Section: Discussionmentioning
confidence: 99%
“…A notable correlation has been observed between positive driving attitudes and a reduction in RTAs, particularly among younger drivers, who are implicated in 60% of accidents. These findings underscore the critical roles of age and education level in influencing RTA rates, indicating that human factors are implicated in up to 95% of traffic incidents (10)(11)(12)14). The grave statistics surrounding RTAs in Pakistan-ranking as the second, sixth, and twelfth leading causes of disability, healthy-lifeyear losses, and premature fatalities, respectively-underscore the urgent need for targeted interventions.…”
Section: Introductionmentioning
confidence: 86%